Penanaman Nilai Antikorupsi Melalui Al-Islam Kemuhammadiyahan di Sekolah Dasar Muhammadiyah Se-Kapanewon Depok Yogyakarta - Suyitno Suyitno; Trisna Sukmayadi (Universitas Muhammadiyah Magelang, 2022)
Understanding and practicing Islamic teachings greatly influences every action. The higher the level of understanding and practice of Islamic values ​​will be proportional to the level of honesty, so it is expected to be able to suppress acts of corruption. This study aims to describe how to instill anti-corruption values ​​through Al Islam Muhammadiyah in Muhammadiyah Elementary Schools in Depok Sleman. The research subjects were all Al Islam Muhammadiyah teachers at Muhammadiyah Elementary Schools throughout Depok, Sleman. This research is a qualitative descriptive study. The results of the study stated that 1) How to instill anti-corruption values ​​through contextual learning in Al Islam Muhammadiyah lessons. 2) The impact of the integration of Islamic values ​​and anti-corruption values ​​is to increase faith and piety in words, attitudes and behavior and avoid corrupt actions.